2016
DOI: 10.1210/en.2016-1245
|View full text |Cite
|
Sign up to set email alerts
|

G6PC2 Modulates Fasting Blood Glucose In Male Mice in Response to Stress

Abstract: The glucose-6-phosphatase catalytic 2 (G6PC2) gene is expressed specifically in pancreatic islet beta cells. Genome-wide association studies have shown that single nucleotide polymorphisms in the G6PC2 gene are associated with variations in fasting blood glucose (FBG) but not fasting plasma insulin. Molecular analyses examining the functional effects of these single nucleotide polymorphisms demonstrate that elevated G6PC2 expression is associated with elevated FBG. Studies in mice complement these genome-wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 28 publications
3
18
0
Order By: Relevance
“…We have previously shown that male 129SvEv G6pc2 KO mice have reduced FBG but no change in FPI relative to WT littermates (Boortz et al 2016a). When this analysis was repeated using female 129SvEv chow fed mice this same reduction in FBG was observed in G6pc2 KO mice (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…We have previously shown that male 129SvEv G6pc2 KO mice have reduced FBG but no change in FPI relative to WT littermates (Boortz et al 2016a). When this analysis was repeated using female 129SvEv chow fed mice this same reduction in FBG was observed in G6pc2 KO mice (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Despite 13 weeks of high fat feeding a comparison between female (Fig. 1D) and male (Boortz et al 2016a) chow fed with female (Fig. 1F) and male (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations